BAHAN AJAR SEBAGAI BAGIAN DALAM KAJIAN PROBLEMATIKA PEMBELAJARAN SINTAKSIS - Eva Juliana (Jurnal Hata Poda, 2022)
This study aims to know and master teaching materials as part of the study of syntactic learning problems. This study uses a type of qualitative research to build knowledge through understanding and discovery. The subjects in this study were lecturers and students. Lecturers and students were used as the main research subjects because the informants were the executors of the teaching and learning process, especially the lecturers as the implementation of the development of teaching materials. The data collection method is through observation and part of the literature review related to the focus of this research. The results of this study indicate that teaching materials are part of the study of the problems of syntactic learning. This is because choosing and determining teaching materials is a problem that educators often face in the learning process. The success of the learning process depends on the design and arrangement of teaching materials. Teaching materials can be interpreted as any form of material that is arranged systematically which allows students to learn independently and is designed in accordance with the applicable curriculum.Keywords: Teaching materials, syntax learning problems.